SARS-CoV-2 in Mozambican primary school-aged children at Maputo City and Province: a cross-sectional study from a low-income country - Adilson Fernando Loforte Bauhofer; Édio Ussivane; Assucênio Chissaque; Fátima Iahaia; Ramígio Pololo; Fernanda Campos; Emerson Miranda; Luciana António; Plácida Maholela; Aline Gatambire; Marlene Djedje; Fátima Ráice; et al. (BMC, 2024)
Abstract Background Seroprevalence studies provide information on the true extent of infection and capture demographic and geographic differences, indicating the level of immunity against Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). We sought to provide local evidence of SARS-CoV-2 exposure in school-aged children during in-class teaching in Maputo City and Province, Mozambique. Methods Between August and November 2022, we performed a cross-sectional study in school-aged children in four schools in rural, peri-urban, and urban areas of Maputo City and Province. A point-of-care test was used to evaluate SARS-CoV-2 antigens and anti-SARS-CoV-2-specific immunoglobulin M (IgM) and immunoglobulin G (IgG) antibodies. Descriptive statistics were used to estimate the prevalence of the antigens and antibodies. Multiple logistic regression models were used to estimate the adjusted odds ratio (AOR) for the factors associated with anti-SARS-CoV-2 antibodies. Results A total of 736 school-aged children were analyzed. The prevalence of the SARS-CoV-2 antigen was 0.5% (4/736). The prevalence of SARS-CoV-2 antigens was 0.0% (0/245), 0.8% (2/240) and 0.8% (2/251), in the rural, peri-urban and urban areas respectively. The overall seroprevalence of the anti-SARS-CoV-2 antibodies (IgG or IgM) was 80.7% (594/736). In rural area anti-SARS-CoV-2 IgG or IgM antibodies were detected in 76.7% (188/245), while in peri-urban area they were detected in 80.0% (192/240) and in urban area they were detected in 85.3% (214/251). In the adjusted logistic regression model, school-aged children from the urban area were more likely to have anti-SARS-CoV-2 IgG or IgM antibodies than were school-aged children from the rural area (adjusted odds ratio: 1.679; 95% CI: 1.060-2.684; p-value = 0.028). Conclusions During the in-class teaching period, active SARS-CoV-2 cases in school-aged children were observed. More than half of the school-aged children were exposed to SARS-CoV-2, and SARS-CoV-2 was significantly more common in the schools at the urban area than in the school in the rural area at Maputo City and Province.